Participation of Renewable Energy Sources in Restructured Power System - Sandeep Bhongade; B. Tyagi (International Journal of Applied Power Engineering (IJAPE), 2013)
In the present paper, a frequency control method based on Genetic Algorithm (GA) has been presented. The proposed scheme has been successfully tested on well known IEEE 39- bus test system. A deregulated electricity market scenario has been assumed in the test system. It has been assumed that both the generators and the consumers are participating in the frequency regulation market. Simulation results show that the proposed GAPID Controller along with HVDC link improves the system frequency. The performance studies have been carried out by using the MATLAB SIMULINK for transactions within and across the control area boundaries.